The effect of transcutaneous electrical nerve stimulation on fatigue recovery in recreational rowers - Zhou, Yinan; Mao, Xinyu; Luo, Wen; Qu, Kaiyuan; Lu, Anqi; Zang, Jiayu; Chen, Yu; Wu, Rui; Wang, Dan (PeerJ, 2025)
Background The quadriceps muscle group plays an important role in rowing performance but is also susceptible to fatigue. Transcutaneous electrical nerve stimulation (TENS) has been shown to be effective in delaying the onset of fatigue, suggesting it may play a role in fatigue recovery after exercise. This study aimed to assess the effects of TENS on quadriceps recovery following a 2000-m rowing ergometer exercise. Methods Twenty-eight recreational rowers were randomly allocated in a TENS group and a sham-TENS group. Following a 2000-m rowing ergometer exercise, the TENS group immediately received a 20-min TENS intervention, while the sham-TENS group received a placebo TENS. Ratings of perceived exertion, blood lactate (BLa), heart rate, the peak torque of knee extensors, and the surface electromyography (sEMG) activity (vastus lateralis and rectus femoris) of both limbs were recorded before and immediately after the exercise, and after the intervention. Results The TENS group showed a superior recovery in muscle strength (increased 20.76% vs 9.44%, F(2, 106) = 11.549, p < 0.001, η2p = 0.179) and BLa (reduced 7.93 vs. 6.34 mmol/L, F(1, 26) = 6.768, p = 0.015, η2p = 0.207) when compared to sham-TENS. However, no time by group interaction was observed in EMG responses in both time (F(2, 214) = 1.268, p = 0.268, η2p = 0.012) and frequency (F(2,214) = 0.997, p = 0.371, η2p =0.009) domains. Conclusion A TENS intervention may be effective in facilitating recovery from quadriceps muscle fatigue in recreational rowers. Thus, it could serve as an alternative recovery treatment to enhance fatigue recovery in recreational rowers.
Keywords: Electrical stimulation; Fatigue; Rowing; Surface electromyography; Muscle strength